Fertilization rate and larvae abnormalities rate for Paracentrotus lividus sea urchin when using cryopreserved sperm - Bogdaniuk, Anastasiia; Shapovalova, Natalia; Marchenko, Olena; Paredes, Estefania (Problems of Cryobiology and Cryomedicine, 2022)
Probl Cryobiol Cryomed 2022; 32(4):295